The association between cardiovascular risk factors and high blood pressure in Singapore's youths - Ang, Jia Ying (2017)
Background: High blood pressure (HBP), is a major risk factor for cardiovascular diseases such as stroke and coronary heart disease. The development of HBP can be contributed by various modifiable risk factors such as overweight/obesity, abdominal obesity and physical inactivity. While HBP may not be as common among the younger population, they may still have cardiovascular risk factors (CRF) that can potentially lead to the development of HBP in future. Purpose: (1) To assess the association between the number of CRF (overweight/obesity, abdominal obesity and physical inactivity) and the risk of developing HBP in Singapore’s youths, (2) To identify the CRF with the strongest association with blood pressure in youths. Method: 213 participants aged 18-35 participated in the study. They were required to complete a physical activity questionnaire and had their height, weight, waist circumference and blood pressure measured. Following which, participants were group based on risk factor category and score for analysis. Results: Individuals with two or three CRF had significantly higher mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) as compared to those with zero or one CRF. In addition, the sum of risk factor had a positive correlation (p < 0.001) with both SBP and DBP readings. Among the CRF, abdominal obesity had the strongest correlation with blood pressure in youths. Conclusion: An increase in the number of CRF was associated with higher blood pressure values, hence increasing the risk of developing HBP in youths.